Assessment of the effects of two different doses of methotrexate in rat ovarian tissue: A histological study (Annals of Medical Research, 2024)
Aim: The use of methotrexate (MTH), a drug commonly prescribed to treat rheumatoid arthritis, cancer, and certain autoimmune diseases, has been linked to early ovarian failure and infertility in women when used in varying amounts and durations. In this study, the possible effects of MTH exposure at different doses on rat ovary were investigated histologically and immunohistochemically.Materials and Methods: A total of 21 female rats, Wistar albino, were utilized in the investigation. The control group (n = 7) was not subjected to any treatment. The 10 mg/kg MTH group (n = 7) and the 20 mg/kg MTH group (n = 7) were given intraperitoneal injections of 10 mg/kg and 20 mg/kg methotrexate, respectively. Five days after injection, the ovarian tissues were taken out of the anesthetized rats and subjected to routine histological tissue processing. The histological evaluation was performed with hematoxylin and eosin (H&E) and Masson's trichrome (MT) on paraffin block sections. Additionally, immunohistochemical staining was performed to determine AMH immunoreactivity.Results: In both MTH groups, histopathological changes were observed, particularly in the 20 mg/kg group, and these included the presence of areas of edema as well as dilated or congested blood vessels. Furthermore, the 20 mg/kg MTH group exhibited increased fibrotic tissue in the ovarian medulla. The number of follicles and AMH immunoreactivity were observed to be reduced in the MTH groups, with the reduction reaching a statistically significant level in the 20 mg/kg MTH group ovary. In terms of AMH immunoreactivity, it is demonstrated that there is no statistical significance between the control and 10 mg/kg MTH groups.Conclusion: The dose of MTH should be considered carefully, as increasing the dose may lead to deterioration of ovarian histopathology and a reduction in the reserve of the ovary.
Keywords: Anti-Mullerian hormone; Methotrexate; Ovarian reserve